Biodiversity of Potential Vectors of Rickettsiae and Epidemiological Mosaic of Spotted Fever in the State of Paraná, Brazil - Liliane Silva Durães; Liliane Silva Durães; Karla Bitencourth; Frederico Rodrigues Ramalho; Mário Círio Nogueira; Emília de Carvalho Nunes; Emília de Carvalho Nunes; Gilberto Salles Gazêta; Gilberto Salles Gazêta (Frontiers Media S.A., 2021)
Spotted Fever Rickettsioses (SFR) are diseases caused by bacteria of the genus Rickettsia, and are transmitted mainly by ticks. Its eco-epidemiological scenarios vary spatially, and may also vary over time due to environmental changes. It is the main disease transmitted by ticks to humans in Brazil, with the state of Paraná (PR) having the sixth highest number of notified incidences in the country. However, information is lacking regarding the SFR disease cycles at likely infection sites within PR. During case investigations or environmental surveillance in PR for SFR, 28,517 arthropods were collected, including species known or potentially involved in the SFR cycles, such as Amblyomma sculptum, Amblyomma aureolatum, Amblyomma ovale, Amblyomma dubitatum, Amblyomma parkeri, Ctenocephalides felis felis, and Rhipicephalus sanguineus sensu lato. From these Rickettsia asembonensis, Rickettsia bellii, Rickettsia felis, Rickettsia parkeri strain Atlantic Rainforest and Candidatus Rickettsia paranaensis were detected. Ectoparasite abundance was found to be related with specific hosts and collection environments. Rickettsiae circulation was observed for 48 municipalities, encompassing 16 Health Regions (HR). As for socio-demographic and assistance indicators, circulation occurred largely in the most urbanized HR, with a higher per capita Gross Domestic Product, lower Family Health Strategy coverage, and with a higher ratio of beds in the Unified Health System per thousand inhabitants. For environmental variables, circulation occurred predominantly in HR with a climatic classified as "subtropical with hot summers" (Cfa), and with forest type phytogeographic formations. In terms of land use, circulation was commonest in areas with agriculture, pasture and fields and forest cover. Rickettsiae were circulating in almost all hydrographic basins of PR state. The results of this study provide the first descriptive recognition of SFR in PR, as well as outlining its eco-epidemiological dynamics. These proved to be quite heterogeneous, and analyzed scenarios showed characteristics strongly-associated with the outbreaks, with cases presenting clinical variation in space, so illustrating the complexity of scenarios in PR state. Due to the diversity of the circumstances surrounding SFR infections in PR, public health initiatives are necessary to foster a better understanding of the dynamics and factors effecting vulnerability to SFR in this Brazilian state.